Modeling electrospun nanofibers: An overview from theoretical, empirical, and numerical approaches - Mohammadzadehmoghadam, S.; Dong, Yu; Davies, I. (Taylor & Francis, 2016)
Electrospinning is a sophisticated material process to manufacture well-tailored nanofibers for fiber reinforcement, tissue scaffolding, drug delivery, nanofiltration, cosmetics, and protective clothing. Abundant information and knowledge are reported from experimental observation and material characterization to determine and control nanofiber properties. However, experimental results need to be interpreted systematically through theoretical, analytical, and numerical models for the optimization of fiber diameter and alignment, porosity, and estimation of mechanical properties of electrospun nanofibers. This paper provides a comprehensive review on current status of modeling approaches used in electrospun nanofibers to elucidate their systematic research approaches including material fabrication, experimental characterization, and modeling.